Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/jgs.14594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi on Cognition and Fall Risk in Older Adults with Mild Cognitive Impairment: A Randomized Controlled Trial

Abstract: Combined center- and home-based Tai Chi training three times per week for 15 weeks significantly improved cognitive function and moderately reduced physiological fall risk in older adults with multiple-domain a-MCI. Tai Chi may be particularly beneficial to older adults with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
192
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(205 citation statements)
references
References 36 publications
4
192
0
Order By: Relevance
“…Some variables such as physical activity level and mobility were not related to falls despite significant relationship with FOF, which might be caused by insufficient statistical power as stated above. Considering mean difference between groups with and without fall history, statistical significant relationship would be drawn with more sample as previously reported studies (Hedman et al., ; Sungkarat et al., ). Thus, nursing interventions can reduce falls as well as a FOF.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some variables such as physical activity level and mobility were not related to falls despite significant relationship with FOF, which might be caused by insufficient statistical power as stated above. Considering mean difference between groups with and without fall history, statistical significant relationship would be drawn with more sample as previously reported studies (Hedman et al., ; Sungkarat et al., ). Thus, nursing interventions can reduce falls as well as a FOF.…”
Section: Discussionmentioning
confidence: 85%
“…Extrinsic factors, which are environmental factors, include poor foot wear, slippery floors, poor lighting (Ambrose et al., ). Among these factors, some were modifiable factors of falls such as physical function and environmental factors (Keall et al., ; Sungkarat, Boripuntakul, Chattipakorn, Watcharasaksilp, & Lord, ), while others were nonmodifiable factors such as age and sex. Medication use, as well as the above‐stated factors, has been reported as a fall‐related risk factor, which is a modifiable factor.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome assessments were blinded in 20 studies (62.5%) . Thirty studies (93.75%) had a low risk of attrition bias because most studies reported the dropout rate or represented detailed explanations. Overall, 21 studies (65.6%) 16–22,24,25,27–29,33–35,37–40 were recognized as having a low risk of methodological quality, and the remaining studies were deemed to have a low methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…Tai Chi, yoga and strength training are helpful in reducing the levels of FOF and thus minimizes the chances of falling [21][22][23][24][25], but others also have no significant relationship [26,27]. Though it is proposed that sports can imply significant beneficial effects in the elderly population, there is still no agreement on the individualistic impacts of different sports exercises on specific traits of physical abilities of the elderly.…”
Section: Introductionmentioning
confidence: 96%